Ancient maritime symbols in Malay traditional boat in the East Coast, Peninsular Malaysia - Wahab, Mohd Rohaizat Abdul; Ramli, Zuliskandar; Samad, Mohammad Anis Abdul; Supian, Nur Sarahah Mohd; Nasir, Muhammad Nu Man Mohd; Masdey, Siti Salina (Malaysian Institute of Planners, 2018)
The study on decorative arts in Malay culture has been widely discussed by domestic and foreign researchers. However, dedicated discussions on decorative arts on traditional Malay boats are still lacking. This article will discuss the discovery of ancient symbols, which was once used in Malay traditional boat arts, especially in the East Coast, Peninsular Malaysia. The objective of this study is to draw a similarity in the understanding of maritime society around the world about the use of ancient symbols on their boats. This study used a visual analysis approach based on the findings of images resembling ancient symbols that were found in boat decorations around the world. These symbols will be described by their meaning and relevance through the use of the iconographic method. The results of this study reveal the understanding and beliefs of maritime communities around the world that are almost identical in terms of their ancient symbols. One of the artistic uniqueness produced by the Malay community is the creation of ancient symbol in a distinctive way and it is also an iconic feature that is connected to the Malay sailor community in the East Coast.